Lean Green Manufacturing Model Design to Increase Productivity and Environmental Performance of the Bread Agroindustry - Satya , Ririn Regiana Dwi Satya; Norita, Defi Norita; Hernanto, Catur Hernanto; Andary Asvaroza , Andary Asvaroza Munita; Sodikun, Sodikun; Cahyadi, Bambang Cahyadi (JURNAL TEKNIK INDUSTRI, 2025)
PT XYZ is an MSME company engaged in the production of bread in the agroindustry. The company conducts its production process up to 10 cycles per day. The number of breads produced by PT XYZ is seven types of bread. Among the seven types of bread produced, the company encountered numerous obstacles in the production process of chocolate banana-filled bread. Several factors continue to constrain the production process of chocolate banana-filled bread at PT XYZ. Some of these issues are caused by waste generated during the production process. This waste includes defective products, excessive storage, waiting processes, and others. Additionally, the green productivity level of PT XYZ remains relatively low. This is because there are several types of waste, including emissions. The purpose of this study is to streamline the bread production process and increase the company's green productivity index. The methods used to achieve the research objectives are Value Stream Mapping and Green Productivity. The two methods used are a combination that can be done to achieve the research target. Based on the results of observations and data processing conducted, PT XYZ has a bread production process lead time of 819.87 minutes/cycle with a green productivity index of 0.552551473. With the recommendations for improvement provided by the researcher, the company can reduce waste at several points. The results of this study demonstrate that the production process can be reduced by 32.00% and the company's productivity index can increase by 39.47%. PT XYZ can use this series of studies as a reference for considering business continuity in the future.